(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To analyze the potentiating aspects of entrepreneurial activities described by stomal therapist nurses. Method: Qualitative, descriptive-exploratory study, carried out through semi-structured interviews, between January and April 2020, with 26 enterprising stoma therapists, supported by the non-probabilistic technique known as snowball. The collected data were fully transcribed and subsequently treated, applying the thematic content analysis technique. Results: Topics that pervaded the perception of entrepreneurship potential in stomatherapy were related, such as market demand and the vast entrepreneurial field of the specialty; clinical experience; the importance of indication by other patients and professionals; the influence of social media and the feeling of satisfaction with the development of the work activity. Conclusion: The analysis of the data allowed us to conclude that the cited potentiators may be a reflection of the reduced supply of specialized public services to the population, expanding the search for such specialists in a particular way, both by referring other patients and professionals and by searching through the social media, which expands the fields of action of the stoma therapist and can bring more satisfaction with their work as specialists.